2002
DOI: 10.1007/s00425-002-0749-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for production of the phytohormone indole-3-acetic acid by cyanobacteria

Abstract: The ability of cyanobacteria to produce the phytohormone indole-3-acetic acid (IAA) was demonstrated. A colorimetric (Salkowski) screening of 34 free-living and symbiotically competent cyanobacteria, that represent all morphotypes from the unicellular to the highly differentiated, showed that auxin-like compounds were released by about 38% of the free-living as compared to 83% of the symbiotic isolates. The endogenous accumulation and release of IAA were confirmed immunologically (ELISA) using an anti-IAA anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(129 citation statements)
references
References 40 publications
7
115
0
7
Order By: Relevance
“…The ability of cyanobacteria to produce IAA was demonstrated; however, whether green algae have IAAproducing ability remains a controversial topic. [72][73][74] In algal strains (Chlorella sp. ), low IAA levels can considerably promote growth and influence oil content.…”
Section: Iaa In Fungal -Microbial Interactionsmentioning
confidence: 99%
“…The ability of cyanobacteria to produce IAA was demonstrated; however, whether green algae have IAAproducing ability remains a controversial topic. [72][73][74] In algal strains (Chlorella sp. ), low IAA levels can considerably promote growth and influence oil content.…”
Section: Iaa In Fungal -Microbial Interactionsmentioning
confidence: 99%
“…There are many reports of auxin production by cyanobacteria, mainly referring to indole-3-acetic acid (IAA), which is generally synthesized through a tryptophan-dependent pathway (Sergeeva et al 2002;Tarakhovskaya et al 2007). Auxin-like substances were determined in the culture media by Salkowski reagent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some cyanobacteria may produce plant growth-promoting substances (Sergeeva et al 2002). There is currently great interest in developing new associations between cyanobacteria and crop plants (Nilsson et al 2005;Rai and Bergman 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the studied cyanobionts, tryptophan acts as precursor for the synthesis of IAA, followed by its excretion into their surrounding environments. This takes place both in the presence or absence of light, indicating that these cyanobionts possess genes for IAA biosynthesis (Sergeeva et al 2002). The ability to synthesize plant hormones is believed to be a major property of rhizospheric, epiphytic and symbiotic bacteria/cyanobacteria that not only stimulate plant growth, but also play important role as signals in communication between plant host(s) and the relevant microflora (Kravechenko et al 2004;Tsavkelova et al 2006).…”
Section: Discussionmentioning
confidence: 99%